Treatment and outcome of 2904 CML patients from the EUTOS population-based registry - Hoffmann, Verena Sophia; Saußele, Susanne; Hehlmann, Rüdiger (Leukemia, 2017)
The European Treatment and Outcome Study (EUTOS) population-based registry includes data of all adult patients newly diagnosed with Philadelphia chromosome-positive and/or BCR-ABL1+ chronic myeloid leukemia (CML) in 20 predefined countries and regions of Europe. Registration time ranged from 12 to 60 months between January 2008 and December 2013. Median age was 55 years and median observation time was 29 months. Eighty percent of patients were treated first line with imatinib, and 17% with a second-generation tyrosine kinase inhibitor, mostly according to European LeukemiaNet recommendations. After 12 months, complete cytogenetic remission (CCyR) and major molecular response (MMR) were achieved in 57% and 41% of patients, respectively. Patients with high EUTOS risk scores achieved CCyR and MMR significantly later than patients with low EUTOS risk. Probabilities of overall survival (OS) and progression-free survival for all patients at 12, 24 and 30 months was 97%, 94% and 92%, and 95%, 92% and 90%, respectively. The new EUTOS long-term survival score was validated: the OS of patients differed significantly between the three risk groups. The probability of dying in remission was 1% after 24 months. The current management of patients with tyrosine kinase inhibitors resulted in responses and outcomes in the range reported from clinical trials. These data from a large population-based, patient sample provide a solid benchmark for the evaluation of new treatment policies.
Published: 29 August 2016
Gesehen am 09.08.2018